The Effectiveness of E-Goverment Implementation in Improving Public Services at the Sinjai Regency Communication, Information and Standardization Office - Syamsiah Hasyim; Mukrimah, Mukrimah; Muhlis Hajar Adiputra; Nurfadillah, Nurfadillah (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This study aims to determine the effectiveness of e-government implementation in improving public services at the Sinjai Regency Information and Coding Communication Office. The research method utilized is qualitative, employing a descriptive approach. Data collection was conducted through observation, interviews, and documentation. Informants included the Head of the Sinjai Regency Information and Coding Communication Service, the Head of Application and Informatics, the Head of Public Relations, and the Head of Public and Community Information and Communication. The findings indicate that the effectiveness of e-government implementation in enhancing public services at the Sinjai Regency Information and Coding Communication Office is not yet optimal. This conclusion is based on three indicators: 1) Goal achievement is insufficient, as the targets for smart village initiatives have not been met, and various obstacles remain; 2) The integration and socialization process is inadequate, with many community members still unaware of the e-government implementation; 3) Adaptation is relatively effective, evidenced by the establishment of a website that serves community needs and facilitates public access to information and complaint submissions through technology, eliminating the need for in-person visits. This study is intended to serve as a reference and theoretical comparison for future researchers and to provide the public with insights into the effectiveness of e-government implementation in improving public services at the Sinjai Regency Information and Coding Communication Office.